The Influence of Environmental, Social, and Governance (ESG) Principles on the Performance of Green Sukuk and Shariah Stocks in Indonesia’s Islamic Financial Market - Ilham Febryan (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of sustainable investment is a global phenomenon that has attracted significant attention, including in Indonesia, where there has been an integration of Environmental, Social, and Governance (ESG) principles into sharia financial market. The present study aims to analyse the effects of Environmental, Social and Governance (ESG) factors on the performance of Islamic stocks listed on the Jakarta Islamic Index (JII), and its contribution to Green Sukuk instruments as a sustainable financing innovation. The research method employed a mixed method approach, incorporating both quantitative and qualitative elements. Quantitative analysis was performed using simple linear regression with ESG Risk Rating data of JII member companies and stock returns. A qualitative analysis, meanwhile, was conducted through a meticulous review of official documents, including the Ministry of Finance's Green Sukuk Allocation and Impact Report, as well as publications by the OJK and IDX pertaining to ESG The findings of the study demonstrated that the ESG Risk Rating had a negative but not statistically significant effect on the returns of JII sharia stocks. It is evident that the potential return on sharia stocks was positively correlated with the ESG risk. Moreover, Indonesian Green Sukuk has a consistent history of experiencing oversubscription, yielding competitive returns, and allocating funds towards sustainable projects in the transportation, renewable energy, and climate resilience sectors. The findings of this study demonstrate that the implementation of ESG can enhance the appeal of sharia-compliant stocks and strengthen the credibility of Green Sukuk within the global market.